Correlation Between Intimate Partner Violence During Pregnancy and Parental Acceptance by Primiparous Mothers - Masomah Jalili; Shahnaz Kohan; Mohammad Javad Tarrahi; Fatemeh Torabi (Iranian Journal of Medical Sciences, 2024)
Background: Pregnancy and the transition to parenthood are periods in parents’ lives that require tremendous adjustment. The physical and mental health of mothers during these periods is significantly associated with maternal acceptance. The present study aimed to evaluate the correlation between intimate partner violence (IPV) during pregnancy and parental acceptance by primiparous mothers in Isfahan, Iran.Methods: A cross-sectional descriptive and correlational study was conducted from September 2021 to February 2022 in Isfahan, Iran. The target population was primiparous mothers in the postpartum period referred to nine different health centers across Isfahan. The participants (n=308) completed three questionnaires, namely demographic, Tabrizi intimate partner violence screening, and parental acceptance questionnaire. Data were analyzed using descriptive and inferential statistics with SPSS software (version 22.0). P<0.05 was considered statistically significant.Results: The mean score of total IPV was 40.45±28.94. Domestic violence during pregnancy was reported by 59 (19.2%) mothers. The most common types were psychological violence (74.4%), followed by financial abuse (35.1%), sexual violence (17.2%), and physical violence (14.9%). The mean score of parental acceptance was 115.77±12.58. There was a significant inverse correlation between parental acceptance and IPV score (r=-0.15, P=0.005). The number of siblings and birth order had a significant inverse correlation with parental acceptance (r=-0.13, P=0.002; r=-0.13, P=0.002, respectively). Moreover, the age difference between the mothers and their next siblings had a significant direct correlation with parental acceptance (r=0.12, P=0.003).Conclusion: Primiparous mothers subjected to IPV during pregnancy had lower parental acceptance after delivery.